Pengaruh Beauty Influencer Review di Instagram Pada Keputusan Pembelian Terhadap Produk Milky Gel Lip Tint Merek X - Dara Eminanda Minardi; Mari Okatini Armandari; Lilis Jubaedah (Departement of Mathematics Education, 2024)
The development of lifestyle and technology has caused changes in people's lifestyles in general, which is marked by more and more people using the internet to access social media, surf or browse, and contact relatives or friends. Currently, social media is a tool or media that is very effective in supporting the process of communication between people, such as between one person, between influencers, between celebrities and their followers and netizens as a whole. One of the influencers on social media is in the field of beauty or beauty influencers. The most sought-after review in the field of decorative makeup beauty by the public is lip cosmetics. Cosmetics for lips have many types such as, lip sticks, lip creams, lip balms, lip gloss and lip tints. The lightest lip cosmetics that have a natural result are lip tints. Therefore, this study was conducted to determine the influence of beauty influencers on Instagram on purchasing decisions on Secondate Beauty brand milky gel lip tint products. This is a beauty influencer review on Instagram of UNJ Cosmetology students affecting the purchase decision of the Secondate Beauty brand milky gel lip tint product.